Sustainability of the Nigerian Environmental Resources Conservation and Management: Interrogating the Principles of Conservation in Biblical Christian Perspective - Rimamsikwe Habila Kitause; Comfort Kamimi Gemade; Franca Shiminenge Jando (European Scientific Journal, ESJ, 2020)
Human environments everywhere are seriously being abused due to different kinds of environmental pollutions which man indiscriminately unleashes on them thereby making these environments almost unsafe and inhabitable engendering unfavourable atmosphere for man’s survival. This paper examines how depreciated Nigerian environmental resources have become nowadays and how this is contributing in making life unbearable in this 21st century. This study adopts descriptive and analytical approaches which were basically employed to describe the phenomenon of environmental destruction and conservation, interpret and analyse data in the study. There were also the use of personal observations, in-depth interviews and focused group discussions on the subject. It was found out that due to the expansion of Christianity which finds expression in the proliferation of churches and ministries in Nigeria, encroachment of all kinds into forest reserve areas is steadily ongoing which is the destruction of the environments. Each denomination and ministry competes over acquisition of large land mass running to hundreds of hectares for either camp grounds for their church retreats or for the establishments of church-based business centres, filling stations, bakery, Television centres, primary schools, secondary schools, colleges and universities thereby depleting the environments. The results show that there is a destruction of the environment on the one hand and the conservation of same on the other hand. The findings show the environmental crisis devastates living organisms which is gradually engendering the total collapse of human environment if no quick attention is given to its proper management. The paper submits that the quicker attention is given in taking better care of the environmental resources by the government, organizations and individuals, the sooner the world becomes inhabitable for human beings.